Avaliação da adequação de sistemas construtivos em madeira na produção de edificações em ilhas oceânicas: estudos de caso no Atol das Rocas e nos Arquipélagos de Fernando de Noronha e de São Pedro e São Paulo - Woelffel, Anderson Buss (2011)
Since ancient times, wood has been widely used by civilizations as a building and decorative material. Currently, when the concern about the preservation of resources of the planet is being more and more debated in several forums, the use of wood - mainly as a building material from renewable and reusable source of low power consumption and high efficiency – has become an issue and has been justified before the challenges imposed by the ideals of sustainable development. Due to the necessity of occupying the oceanic islands motivated by scientific, economic or strategic interests and the consequent need for building support to enable human life in these places, this work is aimed at studying the suitability of wood construction systems employed in those buildings in terms of logistics, environment, safety, comfort and durability, considering especially the fragility of the islands. Methodologically, this research is divided into three steps: recognition (literature and documents), development (data collection using the Post-Occupancy Evaluation Methodology and in situ measurements), and a conclusion (data assessment and publication of results). The studies were performed in Fernando de Noronha Archipelago, St. Peter and St. Paul Archipelago, and Rocas Atoll Marine Biological Reservation. According to the results of this study, it was concluded that wood has satisfactory characteristics for the sites mentioned above, particularly for enabling pre-fabrication, which allows pre-assembling for testing still on shore and subsequent assembling in situ, as well as relocating it with minimal damage to pieces, if necessary. It was also considered the resistance to local conditions and the need for low maintenance, which reinforced the conclusions of this research. It is noteworthy the high resistance/density ratio compared to other materials, favoring the transportation and sizing of pieces, and that the wood is an environmentally friendly material, a good thermal insulator and pleasant feeling to the touch allowing further a building with optimal harmonic relationship with the local landscape, safety and minimal environmental impact.